การพัฒนารูปแบบบทเรียนคอมพิวเตอร์ช่วยสอนแบบอัจฉริยะด้วยการเรียนจากกรณีศึกษา เพื่อเสริมสร้างความรู้ในการให้คำปรึกษาด้านสื่อการเรียนการสอน สำหรับอาจารย์นิเทศก์ระดับประถมศึกษา - บริบูรณ์ ชอบทำดี (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
The purpose of this research is to develop of an intelligent computer-assisted instruction model using case-based learning to enhance instructional media consultation for elementary school supervisors. The number of 397 elementary school teachers in the Department of Social Religion and Culture Studies was randomly selected. The sampling group used for data mining test consisted of 295 supervisors, and another group employed in testing intelligent computer-assisted instruction was comprised of 30 supervisors. The data were analyzed by using percentage, means, standard deviation (S.D.), t-test, K-means, Decision Tree, and Apriori. The results indicated that: 1. In the utilization of instructional media, non- projected material was selected. The most instructional media that the teachers selected to use was photogram and the instructional media mostly used in projected and equipment were projectors. In multimedia, the instructional technology that the teachers mostly used were computer-assisted instruction and the instructional technology that the teachers frequency used was PowerPoint. 2. The intelligent computer-assisted instruction model using case-based learning to enhance instructional media consultation for elementary school supervisors was divided into four modules: 1) communication module is an interaction between an intelligent computer-assisted instruction and supervisors such as mouse clicking, inputting text, doing test, and massage displaying. 2) supervisor module is the record of their supervisors’ information such as data management mechanisms consisting of data storage and data presentation. Supervisor diagnostic mechanism consisted of the score from the test, diagnosing supervisors, model of supervisors, classification of supervisors, grouping of supervisors, association rule and the prediction of supervisors. 3) instruction module is the content related to instructional media and teaching method by case study, and 4) the expert module is the module for giving and analyzing consultation process. 3. The result from an intelligent computer-assisted instruction model using case-based learning to enhance instructional media consultation for elementary school supervisors revealed that elementary supervisors can better provide instructional media consultation for post-tests than a pre-tests at .05 significance level.